PLA based biocomposites for sustainable products: A review - Trivedi, Alok Kumar; Gupta, M.K.; Singh, Harinder (Advanced industrial and engineering polymer research, 2023)
In recent decades, demand for sustainable materials in place of low cost and high strength materials has been trigged globally, which has motivated researchers towards biocomposites/green composites. The PLA has been the most promising matrix material for suistanable biocomposites owing to its biodegradability, good availability, eco-friendliness, antibacterial property, and good mechanical and thermal properties. The PLA-based biocomposites are economical, full/partial biodegradable depends upon types of reinforcement, light in weight, and also offer good thermal and mechanical properties. A number of research works have been performed on PLA and its biocomposites to explore their potential for sustainable products. However, no comprehensive review with up-to-date research data on PLA and its biocomposites are reported so far. This fact motivated to summerize the reported studies on PLA and its biocomposites. The aim of present review is to highlight the current and past trends in the research of PLA and its biocomposites. This review article covers current and past efforts reported by researchers on the synthesis and sustainability of PLA, processing, characterization, applications and future scope of its biocomposites. This study observed that PLA-based composites are the most emerging materials that can replace existing non-biodegradable and non-renewable synthetic materials. The PLA-based biocomposites could be considered as the best source of sustainable products. PLA's mechanical and thermal properties can be enhanced by reinforcing the nano and micro sizes of natural fibers and cellulose.